2019
DOI: 10.1177/1046496419867760
|View full text |Cite
|
Sign up to set email alerts
|

Convergences of Joint, Positive Interactions and Regulation in Collaborative Learning

Abstract: This qualitative study explores the convergences of small groups' joint and positive interactions and regulation in social interaction during collaborative learning. We analyzed the video-recorded social interactions of five groups of student teachers during environmental science tasks. We examined the frequency and functions of the situations in which joint participation and positive socio-emotional interaction converged with regulation (planning, monitoring, and evaluating) in social interaction. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 75 publications
2
23
0
5
Order By: Relevance
“…Other research has shown that co-occurrence of socioemotionally positive interactions and regulation support a meaningful collaborative learning process (e.g. Isohätälä, Näykki, & Järvelä, 2020); this aspect warrants future investigation. In the present study, we also did not consider students' prior knowledge.…”
Section: Forms and Foci Of Metacognitive Regulation (Mr) In Less And More Successful Outcome Groups' Collaborative Learningmentioning
confidence: 79%
“…Other research has shown that co-occurrence of socioemotionally positive interactions and regulation support a meaningful collaborative learning process (e.g. Isohätälä, Näykki, & Järvelä, 2020); this aspect warrants future investigation. In the present study, we also did not consider students' prior knowledge.…”
Section: Forms and Foci Of Metacognitive Regulation (Mr) In Less And More Successful Outcome Groups' Collaborative Learningmentioning
confidence: 79%
“…Third, qualitative research was more heavily embraced and used to investigate phenomena such as groupthink (Lee, 2019), team learning (Zoethout et al, 2017), meetings (Köhler et al, 2012), and collaborative learning (Isohätälä et al, 2020), among others. This marks an important development as the incorporation of qualitative analyses into this traditionally quantitative field can allow deeper insight into the nuances surrounding the complexity of group interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Hadwin et al ( 2018 ) found major diversions in terms and definitions in contemporary research related to social aspects of regulation: for example, socially shared regulation has been considered as social regulation or interpersonal regulation. Similarly, socio-emotional interaction has been operationalized in various ways: some studies have focused on encouragements, compliments, or acts of politeness as positive socio-emotional interaction (Isohätälä et al, 2020 ), while some studies additionally include elements of cohesive participation as signs of positive socio-emotional interaction (Sinha et al, 2015 ). Similarities and conflicts between concepts are also debatable: it is often argued that empathy helps people better understand others, but Bloom ( 2016 ) argues that trying to feel the pain of others can distort our reasoning, make us biased, tribal, and even cruel.…”
Section: Interdisciplinary Efforts For Social Sensitivitymentioning
confidence: 99%